PENGARUH EXERCISE THERAPY MENGGUNAKAN PROVOKING ANKLE STRATEGY DAN COORDINATION THERAPY TERHADAP TINGKAT KELINCAHAN PEMAIN FUTSAL DI KOTA MALANG PASCA CEDERA SPRAIN ANKLE - Mahfud, Achmad -; Raharjo, Slamet; Surendra, Surendra (JP.JOK (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2018)
This is due to the rehabilitation is not followed by the exercise therapy. effect of exercise therapy using provoking ankle strategy and coordination therapy on the futsal player agility after sprained ankle injury. Study was conducted in Malang City. This research used pre-experimental One group pretest posttest design with the Total sampling technique. Research samples were 4 patients in Physioset Malang City who suffered from sprained ankle. The data were collected using the Illionis Agility Test, and then analyzed by using Paired sample t-test method. The result of statistical analysis (t-Test) on the agility data demonstrated the significance value of 0.016 (< Î± 0.05). Therefore, it can be stated that the research hypothesis was accepted. In other words, treatment therapy has a significant effect on the agility of futsal players in Physioset Malang City.